"Asian" photography in Australia. (2nd January 2021) - Palmer, Daniel
ABSTRACT: This paper charts a variety of photographic encounters between Asia and Australia, exploring the emergence of Asian-Australian photographers in the context of increasing Asian migration to Australia since the 1970s. It focuses on contemporary photographic artwork produced by Asian migrants to Australia and a recurrent interest in family archives. I argue that the work of Asian-Australian photographers grapples with complex and often difficult histories of family migration, holding up a critical mirror to Australian racism and reminding us that how we understand "Australian photography" has always been a cultural question about who is entitled to be called Australian.